FACTORS THAT INFLUENCE THE CHANGES OF STUDENTS’ WRITING - Gusparia Gusparia; Puspa Gundary (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This paper is focused on factors that influence the changes in students’ writing ability. Several factors can affect students’ academic writing, it can come from culture, education, social aspects, and cognitive aspects. Those factors are too broad to be discussed in this paper. Finally, the author tries to describe the factors that are just related to the teaching process. They are materials, media, classroom activities, classroom management, teaching strategy, and teacher‘s approach.